2011
DOI: 10.4269/ajtmh.2011.10-0684
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Indoor Residual Spraying and Insecticide-Treated Nets Provides Added Protection against Malaria Compared with Insecticide-Treated Nets Alone

Abstract: Both insecticide-treated bed nets (ITNs) and indoor residual spraying (IRS) reduce malaria in high malaria transmission areas.1–3 The combined effect of these interventions is unknown. We conducted a non-randomized prospective cohort study to determine protective efficacy of IRS with ITNs (ITN + IRS) compared with ITNs alone (ITN only) in preventing Plasmodium falciparum parasitemia. At baseline, participants provided blood samples for malaria smears, were presumptively treated for malaria, and received ITNs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 18 publications
3
105
0
Order By: Relevance
“…[26][27][28] One of the only prospective cohort studies to assess this combination found that, compared with ITNs alone, ITNs combined with IRS had a protective efficacy of 62% against incidence of P. falciparum parasitemia in western Kenya. 29 A recent study in Ethiopia using cross-sectional surveys found that IRS with DDT combined with ITNs was associated with significantly lower vector density and parasite prevalence compared with ITNs alone. 30 Although previous studies and the results of the current study point to the benefits of IRS over ITNs, it should be noted that bed net ownership and use were relatively high in these settings: for example, in our study, one-half of the children under 5 years slept under an ITN the previous night in the control district, and bed net usage in the IRS districts was even higher.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] One of the only prospective cohort studies to assess this combination found that, compared with ITNs alone, ITNs combined with IRS had a protective efficacy of 62% against incidence of P. falciparum parasitemia in western Kenya. 29 A recent study in Ethiopia using cross-sectional surveys found that IRS with DDT combined with ITNs was associated with significantly lower vector density and parasite prevalence compared with ITNs alone. 30 Although previous studies and the results of the current study point to the benefits of IRS over ITNs, it should be noted that bed net ownership and use were relatively high in these settings: for example, in our study, one-half of the children under 5 years slept under an ITN the previous night in the control district, and bed net usage in the IRS districts was even higher.…”
Section: Discussionmentioning
confidence: 99%
“…be reduced by adjusting for pre-intervention differences in the two groups using multivariate analysis (e.g., [26]). There is, however, no guarantee that this will fully control for confounders that may be unknown or unmeasured.…”
Section: General Considerations On Study Designs For Vector Control Smentioning
confidence: 99%
“…9 Recently, IRS has been shown to be effective in areas of high malaria transmission or to malaria epidemic-prone areas. 10 The government of United Republic of Tanzania through Ministry of Health and Social Welfare (MoH&SW) with the support of the President's Malaria Initiative (PMI) started an IRS intervention program in Muleba district, after the 2006 malaria epidemic using lambda-cyhalothrin capsule suspension (ICON 10 CS), targeting villages prone to malaria epidemics.…”
Section: Introductionmentioning
confidence: 99%